2019
DOI: 10.5539/ijps.v11n2p9
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Optimism and Pessimism and its Relationship to the Quality of Life in Patients with Renal Failure in the Government and Private Hospitals in Irbid

Abstract: The aim of this study was to detect the level of optimism and pessimism and its relation to the quality of life in patients with renal failure in the government and private hospitals in Irbid in light of the variables: gender, age, duration of disease and educational level of patients, the sample of the study consisted of (93) patients with kidney failure, who were randomly selected from the study population. The researchers used optimism and pessimism scale and the quality of life scales, their validity and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…These results suggest that the reason people with high levels of coronavirus stress report greater psychological problems is that they have high levels of psychological inflexibility and pessimism and lower levels of optimism. The theoretical underpinnings of this prediction are that stress may lead to greater psychological inflexibility and pessimism, and lower optimism which may in turn lead to greater psychological problems (Al Jarrah et al 2019;Ingram and Luxton 2005;Levin et al 2014;Yildirim and Alanazi 2018). High levels of optimism and low levels of psychological inflexibility and pessimism may help people to cope with coronavirus stress and foster lower levels of psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the reason people with high levels of coronavirus stress report greater psychological problems is that they have high levels of psychological inflexibility and pessimism and lower levels of optimism. The theoretical underpinnings of this prediction are that stress may lead to greater psychological inflexibility and pessimism, and lower optimism which may in turn lead to greater psychological problems (Al Jarrah et al 2019;Ingram and Luxton 2005;Levin et al 2014;Yildirim and Alanazi 2018). High levels of optimism and low levels of psychological inflexibility and pessimism may help people to cope with coronavirus stress and foster lower levels of psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that people with higher levels of coronavirus-related stress are more likely to view psychological problems with more pessimism and less optimism. This may explain how stress can lead to greater pessimism and how low optimism can result in greater psychological problems [50][51][52][53]. Additionally, the beneficial effects of high levels of optimism and low levels of pessimism suggest the need to think about ways to develop optimism as it can aid individuals in overcoming coronavirus-related stress and attenuate psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 79 Several studies have reported that optimism enables HD patients to maintain positive thinking and attitudes toward the problem. 80 - 82 Furthermore, Glover et al observed a positive relationship between chronic kidney disease health outcomes and optimism. 83 The complexity of the ESRD treatment regimen requires self-efficacy in SCM, which was found in this review to be an important predictor for SCM among HD patients.…”
Section: Discussionmentioning
confidence: 99%